2007
DOI: 10.1111/j.1365-3032.2007.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to olfactory and visual cues by over‐wintered and summer generations of the pollen beetle, Meligethes aeneus

Abstract: Behavioural responses to odours of oilseed rape in bud and flower stage and to green and yellow colours are studied for the two main phenological stages of pollen beetles, Meligethes aeneus, a major pest of oilseed rape, Brassica napus. Over‐wintered individuals oviposit in buds of oilseed rape. Adults of the new generation (i.e. the summer generation) feed on flowers of different plant species before over wintering. In olfactometer experiments, the over‐wintered beetles display a higher preference for odour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The contrasting results by this and other studies might be explained by the different florivores investigated, which use different traits to identify and utilize host plants, and are thus differentially affected by herbivore‐induced plant responses. Adult pollen beetles use vision and scent to identify host plants (Doering et al., ; Jönsson, Rosdahl, & Anderson, ; Piesik et al., ); traits which have been shown to change upon exposure of plants to herbivores (Lucas‐Barbosa et al., ; Schiestl et al., ). Furthermore, pollen beetle adults can probably detect changes in host‐plant quality that result from herbivore infestation (Ekbom, ; Ekbom & Borg, ; Hervé, Delourme, & Cortesero, ; Hervé, Delourme, Leclair, Marnet, & Cortesero, ).…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting results by this and other studies might be explained by the different florivores investigated, which use different traits to identify and utilize host plants, and are thus differentially affected by herbivore‐induced plant responses. Adult pollen beetles use vision and scent to identify host plants (Doering et al., ; Jönsson, Rosdahl, & Anderson, ; Piesik et al., ); traits which have been shown to change upon exposure of plants to herbivores (Lucas‐Barbosa et al., ; Schiestl et al., ). Furthermore, pollen beetle adults can probably detect changes in host‐plant quality that result from herbivore infestation (Ekbom, ; Ekbom & Borg, ; Hervé, Delourme, & Cortesero, ; Hervé, Delourme, Leclair, Marnet, & Cortesero, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we hypothesized that parasitization can indirectly also be influenced by management measures that alter crop growth and crop density. Possible mechanisms for indirect crop management effects can be that (1) better fertilized crops grow faster and show a denser morphology leading to a lower parasitism rate via an increased searching time, (2) an altered crop density may also change microclimatic conditions within the crop stand, influencing parasitoid behaviour, and (3) differently fertilized crop plants may produce different olfactory and visual signals perceived by parasitoids and influence their searching behaviour and ultimately parasitism rates (Ferguson et al 2006;Jönsson et al 2007;Williams et al 2007). Nitrogen availability in the soil has also been shown to increase OSR crop vigour and its ability to compensate for pollen beetle damage (Valantin-Morison et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the context in which the semiochemical is detected, as the behavioural response to an odour can be affected by its concentration (Mauchline et al 2005;Piesik et al 2013) and by visual cues (Jonsson et al 2007). A field trapping experiment showed that the magnitude of the effect of an attractant lure on trap catches of pollen beetle was dependent on the nature of the visual cue (Blight and Smart 1999); baited yellow traps caught more beetles than white traps indicating that pollen beetles have wavelength-specific preferences (Döring et al 2012).…”
Section: Finding Host-plantsmentioning
confidence: 99%